An exploration of the role of uniforms in contributing to the embedding and transmitting of organizational culture - Gibson-Tessendorf, Cornel (Rhodes University, Faculty of Commerce, Rhodes Business School, 2005)
Many companies today are using some form of uniforms for employees. This research is an exploration of the role of uniforms in contributing to the embedding and transmitting of organizational culture. Culture is the experiences and common learning of the organization that results in shared values and beliefs. According to Schein (1985: 14) culture has three levels, namely: artifacts, values, and basic underlying assumptions. The first level of the culture consists of the physical constructs of the organization, and therefore includes the uniforms, which is the focus of this study. Schein (1985: 223) further proposes that culture can be embedded and transmitted through various mechanisms. The research was conducted in the constructivist paradigm, at a tertiary institution of higher learning in Eastern Cape, South Africa. To ensure triangulation, three sources of data were used, namely: documentation; observation; and both individual and focus group interviews. The researcher argues that uniforms played a role in the embedding of the sample organization's three levels of culture, which were expressed in terms of Hofstede's (1991: 07) culture dimensions. Firstly, the use of the different uniforms by different groups, as well as the ranking indicated by the uniforms, played a role in embedding the high power distance culture. Secondly, the symbolism of security portrayed by the uniform played a role in embedding the high uncertainty avoidance culture. Thirdly, it was found that the uniform created unity amongst groups, resulting in greater expression of collectivism. Fourthly, the use of sensible and practical uniforms plays a role in embedding the feminine culture where competitiveness is avoided and relationships are nurtured. Lastly, the uniform plays a possible role in transforming the culture from short-term to a long-term orientation that focuses on the future.
Keywords: Organizational behavior; Corporate culture; Clothing and dress -- Social aspects; Employees -- Uniform; Uniforms